Rates of Mental Illness and Addiction among High-Cost Users of Medical Services in Ontario - Hensel, Jennifer M. (Can J Psychiatry, 2016)
OBJECTIVE: To quantify the burden of mental illness and addiction among high-costing users of medical services (HCUs) using population-level data from Ontario, and compare to a referent group of nonusers. METHOD: We conducted a population-level cohort study using health administrative data from fiscal year 2011-2012 for all Ontarians with valid health insurance as of April 1, 2011 (N = 10,909,351). Individuals were grouped based on medical costs for hospital, emergency, home, complex continuing, and rehabilitation care in 2011-2012: top 1%, top 2% to 5%, top 6% to 50%, bottom 50%, and a zero-cost nonuser group. The rate of diagnosed psychotic, major mood, and substance use disorders in each group was compared to the zero-cost referent group with adjusted odds ratios (AORs) for age, sex, and socioeconomic status. A sensitivity analysis included anxiety and other disorders. RESULTS: Mental illness and addiction rates increased across cost groups affecting 17.0% of the top 1% of users versus 5.7% of the zero-cost group (AOR, 3.70; 95% confidence interval [CI], 3.59 to 3.81). This finding was most pronounced for psychotic disorders (3.7% vs. 0.7%; AOR, 5.07; 95% CI, 4.77 to 5.38) and persisted for mood disorders (10.0% vs. 3.3%; AOR, 3.52; 95% CI, 3.39 to 3.66) and substance use disorders (7.0% vs. 2.3%; AOR, 3.82; 95% CI, 3.66 to 3.99). When anxiety and other disorders were included, the rate of mental illness was 39.3% in the top 1% compared to 21.3% (AOR, 2.39; 95% CI, 2.34 to 2.45). CONCLUSIONS: A high burden of mental illness and addiction among HCUs warrants its consideration in the design and delivery of services targeting HCUs.